Is Marketing Strategies and Business Sustainability are mediated through Entrepreneurial Innovation in Ethiopia? - Kant, Shashi; Dejene, Fisseha; Garuma, Gezu (Journal of Social Sciences and Management Studies, 2023)
In the current study, marketing techniques' effects on the expansion of sustainable enterprises were examined. This was done through the lens of entrepreneurial innovation in a scenario involving a sustainable business in the innovation phase. The researchers developed a number of methodologies, as well as both descriptive and inferential statistics. A simple random sampling mechanism was used by both probability and non-probability sampling techniques. The Ethiopian branch of the Addis Ababa branch of the Digital Banking Sector served as the representative organisation and conducted a survey of 425 Digital Banking Sector clients, those served in sectors, and personnel from current organisations to collect the data for this study. According to the researchers' results, the poor performance of leaders, the workplace, and low employee engagement are primarily to blame for the decline in business sustainability and the application of marketing techniques.  The researchers urged the appropriate body to file an application in order to address the problems with the predictor control, give good implementation of the marketing plan, and then give strong company sustainability.